Οι εγγενείς αξίες του φυσικου περιβάλλοντος και τα καθήκοντα που υπαγορεύονται προς αυτό - Perros, Panagiotis, author; National University at Athens, Greece, publisher (Colorado State University. Libraries, 2004)
Environmental ethics stands on a frontier, as radically theoretical as it is applied. Alone, it asks whether there can be nonhuman objects of duty. Animals, plants, endangered species, ecosystems, and even Earth are progressively unfamiliar as objects of duty, and puzzles arise both for theory and practice. Answers to such questions are as urgent as any humans face, and intimately related to the four principal issues on the world agenda: peace, population, development, and environment.
Environmental ethics: values in and duties to the natural world (summarized with commentary by Panagiotis Perros)
Summarized with commentary in Greek by Panagiotis Perros.
Keywords: nature; species; ecosystems; value theory; environmental values; environmental ethics